Missing and endangered [compact disc, unabridged] - Jance, Judith A. (Jance, Judith A. Joanna Brady mysteries, 2021)
Protecting a brilliant freshman whose homeschooled life has left her unprepared for the outside world, Jennifer invites the vulnerable girl home for a Christmas break that embroils Sheriff Joanna Brady in a volatile missing-persons case.